IS THE LIMITED LIABILITY DOCTRINE APPLICABLE TO COMPANY DIRECTORS? - Virginijus Bite; Gintare Jakuntaviciute (European Scientific Journal, ESJ, 2014)
At all times the majority of directors, which desired to properly perform and develop activities on behalf of a company in a competitive market, were raising relevant questions on how to control a company aiming to guarantee and ensure its financial viability and competitiveness, what is the line between the freedom of decision-making and personal liability therefore, are the directors equally as the shareholders protected under the limited liability doctrine? The prevailing opinion is that principle of limited liability protects shareholders and only shareholders from liability. Therefore, in this study the authors explore this premise from the perspective of the doctrinal implications of immunising directors from personal liability for their actions, when managing company’s affairs. The authors’ principal conclusions are that the limited liability doctrine should be applied not only to the shareholders, but also in respect of the directors. Such legal protection from the liability could be withdrawn, when a director commits illegal acts that cause damages to a company or to creditors thereof. In respect of creditors the liability of such director shall still be considered subsidiary, whereas a direct liability of the director may only arise against a company until its liquidation and only after the completion of liquidation proceedings – against the creditors whose claims remained unsatisfied.